Avian vocal production beyond low dimensional models. (16th February 2017) - Mindlin, Gabriel B
Abstract: Birdsong is an active field of research in neuroscience, since songbirds learn their songs through a process similar to that followed by humans during vocal learning. Moreover, many of the vocalizations produced by birds are quite complex. Since the avian vocal organ is nonlinear, it is sensible to explore how much of that complexity is due to the neural instructions controlling the vocal organ, and how much to its nonlinear nature. In this work we first review some of the work carried out in the last years to address this problem, and then we discuss the existence of noisy sound sources in the avian vocal organ. We show that some spectral features of the song produced by the Zebra finch (one of the most widely studied species) can only be explained when vortex sound is taken into account.